85 лет Малопургинскому району: [альбом фотографий]
Титульного листа нет, описано по обложке Экземпляры: УКП (20160419) / Инвентарный номер: АП20140640 / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: В 76 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)